Charity and poor relief in a context of poverty - Castro, B (2001)
Colombia in the second half of the nineteenth century was a country with extensive poverty and vulnerability was the main characteristic of the poor. A general concern about the conditions of the poor, particularly in urban areas, was broadly manifested. Poverty was seen basically as a moral problem, and poor relief was implemented within a process of moralization. Between 1870 and 1930 poor relief underwent significant transformation: it grew appreciably, became more complex, more dynamic, more professional and more specialized; it passed gradually from being strongly localized to a departmental and national orientation. Poor relief involved the decision from the state to incorporate the 'social' in the government agenda and by 1930 started to be more grounded in political reality. An identifiably modern 'social policy' came into being, even though it contained some ambiguities and traditional values. There were two main forms of poor relief: institutional and outdoor. Institutional poor relief was predominantly carried out by the state and some private societies. Some state poor relief establishments continued to be run by religious orders. Outdoor poor relief was only implemented by private societies and institutions. For poor relief public beneficencia and private charity were equally important. In this period the state attempted to consolidate resources for beneficencia and for social assistance; it created specific poor relief taxes and established special funds. Private giving was linked to traditional Christian charity. Charity was constant, large and participants covered a broad social spectrum. Modern ideas of charity were progressively introduced, generating a professionalization of voluntary activities. Alongside poor relief there were other survival strategies promoted by the poor of which mutual aid societies were the best example. They grew considerably and they gave support to their members in an any eventualities. They were certainly important in the formation of'social capital'. Sources for this research are dispersed; most of them came from institutions, societies, establishments that carried out poor relief activities. Research about poor relief generally and inevitably has to face a lack of informal data on many aspects of the subject, though much can be gained through the study of wills.